CESIUM-137 CONTENT IN MILK - MONITORING AFTER FUKUSHIMA NUCLEAR POWER PLANT ACCIDENT - F. Groppi; S. Manenti; M. L. Bonardi; L. Gini; A. Ioannidou (Marina B. A. Vasconcellos, 2014)
Radionuclides released during an accident can be transported over long distances, before they are deposited by fallout on vegetation and soil. Such an event occurred after the Chernobyl accident in April 1986 where extensive fallout of various long- and short lived radionuclides was observable in many European countries, including Italy. The resulting contamination of the vegetation has decreased due to radioactive decay and weathering. Longer lived radionuclides, however, are still present in the soil and are taken up by plants via their roots. In particular 137Cs that is one of the most important contaminants because of its long half life, affinity for biological system and its uptake to man through diet. In March 2011 Fukushima accident contributed with new input in the atmosphere of contaminants: a cloud containing radioactivity was formed in air over Fukushima nuclear power plant NPP, moved over the Pacific Ocean in the direction of the Arctic Ocean, enter in the Atlantic Ocean and diffused over the European continent. The transferred radioactivity was detectable all over the word: many laboratories started measurements and presented results on the fallout from the Fukushima nuclear accident1. Also in Italy were made a series of measurements of the fission product radionuclides in different regions and places. In particular our research group was focused on measurements of radioactivity present in air, water, snow, soil, grass and milk in Milano and Monte Rosa region. In fresh goat and cow milk produced and collected in a farm at a village in Anzasca valley near Macugnaga (rural area), in Monte Rosa mountain at 500 m height in the period April to July 2011 were found small values of concentration of 131I and 137Cs. The 134Cs/137Cs activity ratios can reveal information on radioisotope origin. The relative high activity concentrations of 137Cs and the very low values of the activity ratio of 134Cs/137Cs, in combination with the absence of 134Cs in most of the cases indicate a strong contribution from “older” ...